Environmental Impact Assessment System in Nepal - An Overview of Policy, Legal Instruments, and Process - Bhatt, Ramesh Prasad; Khanal, Sanjay Nath (Kathmandu University Journal of Science, Engineering and Technology, 2009)
Environmental Impact Assessment (EIA) is one of the major instruments integrated with a goal of making economic development projects environmentally sound and sustainable. The use of EIA began in 1970 in the USA and spread rapidly throughout the world, particularly after the UN Earth Summit held in 1992. To enable such issues to be taken into account in decision-making, it was necessary to introduce a systematic procedure of EIA. Therefore, to date, many countries of the world have a legal and institutionalized system of EIA. In the planning history of Nepal, the Sixth Plan (1980-’85) for the first time recognized the need for EIA integration for major infrastructure projects. The government of Nepal enunciated environment conservation-related policies in the Seventh Plan (1985-90). In order to enforce this policy, a series of guidelines were developed incorporating the elements of environmental factors right from the project formulation stage of development plans. Environmental Assessment Guideline 1993 was the first “lesson learnt” document in Nepal which has played a facilitation role in the EIA process. Until then, international obligations, conventions, guidelines, treaties applied for the environmental and biodiversity conservation measures at the policy level. Inspired by the international conventions, treaties, and planned EIA process internationally; the Nepal government has established an EIA system for developmental projects with the formulation of Environmental Protection Rules 1997 as well as sectoral policy, laws, and guidelines. Based on the formulated Act, regulations, and guidelines, criteria for IEE/EIA has established that the development projects certainly require environmental assessment study as per the nature of the projects unless they cross the given threshold for the disruption of environmentally sensitive areas and their natural environment. Leafing the policies and legal instruments of the country, now the ongoing EIA system has a big challenge towards environmental management and biodiversity conservation for sustainable development.